Functional Genomic Analysis of Aspergillus flavus Interacting with Resistant and Susceptible Peanut - Wang, Houmiao (Toxins (Basel), 2016)
In the Aspergillus flavus (A. flavus)–peanut pathosystem, development and metabolism of the fungus directly influence aflatoxin contamination. To comprehensively understand the molecular mechanism of A. flavus interaction with peanut, RNA-seq was used for global transcriptome profiling of A. flavus during interaction with resistant and susceptible peanut genotypes. In total, 67.46 Gb of high-quality bases were generated for A. flavus-resistant (af_R) and -susceptible peanut (af_S) at one (T1), three (T2) and seven (T3) days post-inoculation. The uniquely mapped reads to A. flavus reference genome in the libraries of af_R and af_S at T2 and T3 were subjected to further analysis, with more than 72% of all obtained genes expressed in the eight libraries. Comparison of expression levels both af_R vs. af_S and T2 vs. T3 uncovered 1926 differentially expressed genes (DEGs). DEGs associated with mycelial growth, conidial development and aflatoxin biosynthesis were up-regulated in af_S compared with af_R, implying that A. flavus mycelia more easily penetrate and produce much more aflatoxin in susceptible than in resistant peanut. Our results serve as a foundation for understanding the molecular mechanisms of aflatoxin production differences between A. flavus-R and -S peanut, and offer new clues to manage aflatoxin contamination in crops.